Assessment of the use of remote sensing methods to protect agricultural lands from invasive plants - Lugovskoy Alexander; Terekhin Mikhail; Perskaya Victoria; Morkovkin Dmitry; Wang Yanmin (E3S Web of Conferences)
The article examines the problems of detecting the contamination of agricultural lands with invasive plants using the example of Sosnowskyi's hogweed. The use of remote sensing methods is proposed, on the basis of which it is possible to build cartographic models for the protection of agricultural lands from invasive plants of various natural zones of the European part of Russia. The article substantiates the position that the optimal application of the method helps to solve the problem of controlling the distribution sites of hogweed and providing cartographic data on of Sosnowskyi's hogweed to the required territory. As a result of the study, the possibility of using this method was confirmed, which most fully displays the group of the mapping object in binary image format, and possible methods to improve the results. It is determined that the binary image format makes it possible to use the automation process in thematic mapping to protect agricultural land from invasive plants of various species, including of Sosnowskyi's hogweed, and to ensure environmentally sustainable agriculture.